Mapa topográfico de sensibilidade dolorosa à pressão no ombro em indivíduos com síndrome do impacto do ombro - Ribeiro, Ivana Leão (2014)
Background: Shoulder pain is one of the most common and disabling complaints, and shoulder impingement syndrome (SI) is one of the most common causes of this symptom. Recently, several records of pressure pain threshold become useful tools as topographical pressure pain sensitivity maps to assess the state of awareness on various musculoskeletal conditions. However, there are no studies that have proposed topographic maps to assess shoulder sensitivity. Objective: To develop topographical pressure pain sensitivity maps of the shoulder in subjects with SI as compared with healthy subjects, and to analyze the intra-rater reliability of the topographic maps of the shoulder in healthy and asymptomatic subjects. Methods: Initially, 29 predetermined points and 4 points in fixed anatomical locations have been identified on both shoulders of 25 patients with SI and 25 healthy and asymptomatic subjects. The map was determined from anatomical landmarks and anthropometric measurements of each individual. Of all 32 points assessed, 11 are located in bony structures, 11 in muscle bellies, 9 in tendons, 1 on the coracoacromial ligament and 1 over the acromioclavicular joint. The pressure pain threshold was evaluated at all points in the dominant and nondominant side of healthy subjects and in the symptomatic and asymptomatic sides in subjects with SI. The sides and points were randomized prior to the evaluation. The pressure pain threshold was assessed 3 times on each point (20 s of rest), and the mean of each measure was considered for analysis. Results: The methodology used allowed us to characterize a topographic map for assessing shoulder pain sensitivity in subjects with SI. There was no difference between the SI and healthy groups (p> 0,05). However, the symptomatic side of subjects with SI showed higher sensitization (p <0.05), in some locations (points 6 and 7, located on the spine of the scapula and point 10, located on the infraspinatus muscle). The tendons were the most sensitive structures, followed by the bones for both groups. There was excellent intra-rater reliability between the trials of pressure pain threshold for each point (non-dominant side of healthy subjects, ICC: 0.86-0.98; dominant side of healthy subjects, ICC: 0.89-0.96). The standard error of measurement and minimal detectable change presented range, respectively, 28.4-55.9kPa and 66.7-131.4kPa (non-dominant side), 29.4-60.8kPa and 69.6-142.2kPa (dominant side). Conclusion: The proposed topographical pressure pain sensitivity maps of the shoulder was useful for detecting the state of peripheral hyperalgesia in different anatomical structures (bones, muscles and tendons) in subjects with SI, and was reliable for assessing pressure pain sensitivity on the shoulder in healthy subjects.